Minimization of power losses in passive power filters - N. P. Boyarskaya; V. P. Dovgun; D. E. Egorov; V. V. Novikov; D. A. Shandrigin (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Broadband passive filters (BBF) are an effective measure to mitigate harmonic resonance in power systems with nonlinear harmonic producing loads. The disadvantage of simple second-order broadband filters are pure selectivity and excessive fundamental frequency losses. This is especially evident in devices designed for low-order harmonics mitigation. This paper presents new broadband filter configurations with superior performances and low fundamental frequency losses.METHODS. A general method of broadband passive filter design is considered. The filter has the form of single-loaded ladder LC-two-port. Conditions of minimal fundamental frequency loss of the filer are determined.RESULTS. This paper presents new broadband filter configurations with superior damping performances and low fundamental frequency losses. Different broadband filter configurations are compared. The results show that 3-5 order broadband ladder filters have better filtering performance and lower power loss than traditional C-type filters.CONCLUSION. The proposed broadband filters can be used for industrial power systems with powerful nonlinear loads. This will normalize the power quality and at the same time improve the energy efficiency of compensating devices.